Kluwek Seed (Pangium edule Reinw) Germination Response to Soaking Time and Concentration of Gibberellin Acid (GA3) - Ratnasari, Tri; Ana, Daniar Alfi; Sulistiyowati, Hari; Setyati, Dwi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2021)
Kluwek seeds (Pangium edule Reinw.) have a low germination percentage caused by dormancy due to hard seed coat. Kluwek seed germination takes about 1 month. The purpose of this study was to obtain a combination of treatments that were effective in increasing the percentage of kluwek seed germination and reducing the intensity of kluwek seed dormancy. This study used a Completely Randomized Design (CRD) factorial design. The first factor was immersion time (H) consisting of five levels, namely H0: Control (0 hour), H1: 6 hours, H2: 12 hours, H3: 18 hours, and H4: 24 hours and the second factor was giberellin concentration (G) with five levels namely G0: 0 ppm, G1: 25 ppm, G2: 50 ppm, G3: 75 ppm and G4: 100 ppm. Data analysis used Analysis of Variance (Anava) and further tested with Duncans' Multiple Range test (DMRT) at a significant level of 5%. The results obtained showed that the percentage of seed germination without immersion is 6.67%. Soaking using aquades produces an average germination percentage of 28.33%. The most effective treatment was GA3 75 ppm for 24 hours with seed germination of 60%, while the value of dormant intensity is 40%.Keywords: dormancy, germination, gibberellin, kluwek.